PERSPEKTIF MUHADDITSIN TENTANG KEDUDUKAN THABAQAH DAN RAWI HADITS - ummu kulsum (Fakultas Agama Islam Universitas Islam Madura, 2021)
The term Hadith is the words of the Prophet, all the actions of the Prophet, and all the conditions of the Prophet, with the existence of the Knowledge of Thabaqah, giving the opportunity for the ahlul hadith to determine the rawi, sanad and matan of a hadith based on a more specific group in the narration of a hadith. Knowledge of thabaqah, 'Ulama look to the glory of friendship with the Prophet, which made all friends dalah thabaqah. In this case it is determined how the rank of thabaqah is based on which level the thabaqah level consists of twelve levels, on the other hand there is a mention of five thabaqah. In Thabaqah and rawi hadiths are determined by the following formulas: 1) how is the attitude of Thabaqah and Rawi Hadith according to Muhaddisin's perspective, 2) How do muhadditsin determine the levels of thabaqah in hadith narrations. Keywords: Knowledge of Thabaqah, Rawi Hadith, The Muhaddithin.